FACTORS ASSOCIATED WITH BIRTH WEIGHT OF CALVES IN NILI RAVI BUFFALOES AT BRI PATTOKI, PUNJAB (Pakistan Journal of Science, 2022)
This study was made to determine the effects of herd, year, season, lactation number and sex on calf’s birth weight in Nili Ravi Buffalo. The data from 1975-2017 was taken in 15525 edited observations of 6932 buffaloes from six institutional herds. The year was divided into four seasons viz (December to February, March to May, June to August and September to November) to evaluate the real effects of herd x year and season. To analyze the data SPSS version 19, statistical package was used. The mean ± S.E of birth weight was calculated as 35.18±.018Kg. The mean of birth weight of male and female calf were as 35.82 ± 0.19Kg and 34.53 ± 0.18Kg, affected by herd-yearseason, sex and lactation number (P
Keywords: Birth Weight; Nili Ravi; Season; Milk Production